Identity Texts and Academic Achievement: Connecting the Dots in Multilingual School Contexts. Issue 3 (15th September 2015) - Cummins, Jim; Hu, Shirley; Markus, Paula; Kristiina Montero, M.
Abstract : The construct of identity text conjoins notions of identity affirmation and literacy engagement as equally relevant to addressing causes of underachievement among low socioeconomic status, multilingual, and marginalized group students. Despite extensive empirical evidence supporting the impact on academic achievement of both identity affirmation and literacy engagement, these variables have been largely ignored in educational policies and instructional practices. The authors propose a framework for identifying major causes of underachievement among these three overlapping groups and for implementing evidence‐based instructional responses. The framework argues that schools can respond to the devaluation of identity experienced by many students and communities by exploring instructional policies and strategies that enable students to use their emerging academic language and multilingual repertoires for powerful identity‐affirming purposes. Drawing on projects involving First Nations and immigrant‐background multilingual students, the authors document the profound transformations in academic, intellectual, and personal identity that multimodal identity text work is capable of engendering.